The nanoparticle formula optimization from Temulawak extract (Curcuma xanthorrhiza) as adjuvant therapy - Swandiny, Greesty Finotory; Nafisa, Safira; Qodriah, Rahmatul; Nugroho, Gumilar Adhi; Bakhtiar, Muhammad Taher (International Journal Labs, 2024)
Temulawak extract was synthesized using temulawak sodium alginate. The nanoparticle formula was obtained by combining the characteristics of temuwak extract and temusawak. The microbeads were characterized by scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy. The size of Alg-Curcuma was measured at SEM. The particle size distribution of the sample was analyzed using FTIR spectra. The results showed that the size of the resulting beads is microparticle in size. It was found that the temurawak extract is a good candidate as an anticancer agent. Therefore, there are several recommendations that can be done to optimize the synthesis of the material. The study reported that the recommended parameter is 12.5 kV with a flow rate of 0.1 mL/h (first batch synthesis).